The Impact of the Job Creation Government Regulation in Lieu of Law No. 2 of 2022 on Severance Pay Entitlements in the Termination of Employment: A Normative-Comparative Analysis and the Framework for Worker Protection in Indonesia - Muhammadnor Fitri; Budi Kristanto, Budi (Al-'Adl, 2025)
The enactment of Government Regulation in Lieu of Law (Perppu) No. 2 of 2022 on Job Creation has fundamentally restructured Indonesia's employment termination and severance payment regime. This article critically examines the normative implications of this regulatory transformation for workers' severance rights, with empirical grounding in Banjarmasin, South Kalimantan. Employing a doctrinal legal research methodology that integrates normative-comparative analysis with primary statutory sources, the study addresses three central questions: What constitutional and statutory rationale underpins the government's issuance of Perppu No. 2/2022? How does the omnibus law mechanism restructure severance entitlements relative to Law No. 13/2003? What legal protections remain available to workers following the regulatory transition? Findings reveal that while the Perppu introduces several pro-investment flexibilizations, it simultaneously diminishes workers' bargaining position and erodes severance certainty. Comparative analysis demonstrates a systematic regression from the Manpower Act of 2003 standards, particularly regarding compensation proportionality, reinstatement rights, and sector-specific minimum wage protections. The study proposes a rights-protective implementation model that reconciles investment facilitation with constitutional worker-protection mandates, offering practical guidance for judges, legal practitioners, and policymakers navigating the post-Perppu regulatory landscape.